2019
DOI: 10.1002/jhet.3574
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Efficient Process for the Synthesis of Novel Heterocycles Containing Benzofuran Moiety Using Thiocarbohydrazide as a Precursor

Abstract: A simple and efficient process for the synthesis of novel heterocycles starting from thiocarbohydrazide was reported. Reaction of 2‐acetylbenzofuran (1) and thiocarbohydrazide (2) in ethanol containing acetic acid produced the corresponding thiocarbohydrazone 3 in 86% yield. Reaction of 3 and isatin (4) gave N,2‐bis(2‐oxoindolin‐3‐ylidene)hydrazine‐1‐carbothiohydrazine (6) in 65% yield, rather than the expected product, 3‐[(1‐methyl‐1‐benzofur‐2‐ylmethylidene)amino]‐1‐{[(3Z)‐2‐oxo‐2,3‐dihydro‐1H‐indol‐3‐yliden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…In view of the wide variety of biological and pharmacological properties of substituted benzofurans and indoles, several methods were reported so far for the synthesis of these compounds. These include C-H activation through intramolecular annulation method for benzofuran, 32 synthesis of novel heterocycles containing benzofuran motif using thiocarbohydrazide as precursor, 33 Zn catalyzed Sonogashira cyclisation strategy for substituted benzofurans and indoles, 34 C-H amination protocol for substituted indoles 35 and so on. Although there are several reviews on the synthesis of substituted benzofurans and indoles, so far no review is reported yet on MW assisted synthesis of these important compounds.…”
Section: Introductionmentioning
confidence: 99%
“…In view of the wide variety of biological and pharmacological properties of substituted benzofurans and indoles, several methods were reported so far for the synthesis of these compounds. These include C-H activation through intramolecular annulation method for benzofuran, 32 synthesis of novel heterocycles containing benzofuran motif using thiocarbohydrazide as precursor, 33 Zn catalyzed Sonogashira cyclisation strategy for substituted benzofurans and indoles, 34 C-H amination protocol for substituted indoles 35 and so on. Although there are several reviews on the synthesis of substituted benzofurans and indoles, so far no review is reported yet on MW assisted synthesis of these important compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Mono-and bis-(thiocarbohydrazones) based on 2-acetylpyridine have antioxidant activity are described [11]. Preparation of thiocarbohydrazones containing benzofuran heterocycles was reported [12]. Thiocarbohydrazone-1-(4-arylidene)-5-(2-oxoindolin-3-ylidene) having antidiabetic properties was explained [13].…”
Section: Introductionmentioning
confidence: 99%